Mosby's drug guide for nurses - Skidmore-Roth, Linda (St. Louis, Missouri : Elsevier Mosby, 2011)
Offers access to information on 50 drug classifications and more than 4,000 individual generic and trade name drugs. This title features color illustrations that shows how drugs work at the cellular level, and a photo atlas that depicts physical landmarks and techniques for safe and effective drug administration.
Color Insert Immunization Schedules for Children and Adolescents -- Mechanism and Sites of Action -- Photo Atlas of Drug Administration -- Individual Drug Monographs -- Drug Categories.
Includes index.
Keywords: PHARMACEUTICAL PREPARATIONS; DRUG THERAPHY HANDBOOKS